Synthesizing foundations in evolutionary morphology and a plea for conceptual explicitness regarding homology concepts - Göpel, Torben (Frontiers in Ecology and Evolution, 2024)
Morphology, the scientific discipline dealing with description and comparison of organismal form, is one of the oldest disciplines in biology and traditionally strongly linked to the concept of homology.With morphological data being used and morphological knowledge being applied in other (younger) biological disciplines, morphology has often been degraded to an only auxiliary discipline or a mere set of methods serving those other disciplines. While this notion has been wrong all along, the last decades have seen a renaissance of morphology mostly due to significant leaps in imaging techniques and the advent of 3D digital data. Modern large-scale morphological endeavors in what is called phenomics and new means of functional analyses underline the fruitfulness of morphological research.Furthermore, morphology has been revisited on a conceptual level leading to a "re-philosophication" of morphology acknowledging its nature as explanatory science. Based on Richter & Wirkner's research program of Evolutionary Morphology, this essay expands the conceptual framework to identify entities and processes vital for morphology as independent scientific discipline. With no unified homology concept in sight (and maybe not even desired), following the emergence of bioontologies in morphology, a plea is made for conceptual explicitness which acknowledges the plurality of homology concepts but enables intersubjective transfer.